Pharmacological targets and therapeutic mechanisms of Arabic gum in treating diabetic wounds: insights from network pharmacology and experimental validation - Chai, Langjie; Chen, Danyang; Ye, Lili; Peng, Pan; Wang, Haijie; Al Saleh, Nouf; Al-Kenani, Nader S.; Guo, Jia; Li, Qianqian; Guo, Liang (Frontiers in Pharmacology, 2025)
Background and objectivesOn account of the long-term inflammatory microenvironment, diabetic wounds are challenging to heal in which advanced glycation end products are considered important factors hindering the healing of diabetic wounds. Gum Arabic has demonstrated significant potential in the treatment of various diseases owing to its anti-inflammatory and antioxidant properties. Nonetheless, there is still insufficient research on the role of Arabic gum in facilitating diabetic wounds healing and its mechanisms. This study aims to investigate the pharmacological targets and therapeutic mechanisms of Arabic Gum on diabetic wound healing by adopting network pharmacology, molecular docking, and experimental validation.MethodsKey active components of Arabic Gum and disease targets were identified through network pharmacology and bioinformatics. GO/KEGG enrichment was performed to identify critical pathways. Cytoscape and AutoDock were used for targets prediction and molecular docking validation. In vitro, Transwell assay and tube formation assay were performed to evaluate the effect of Arabic Gum on human fibroblasts migration and human umbilical vein endothelial cells angiogenesis. Western blotting analyzed Pro-caspase-1, ASC, NLRP3 and NF-κB pathway-related proteins. In vivo, a full-thickness diabetic wound model was established. Histological changes were assessed via H&E and Masson’s staining, oxidative stress levels through DHE staining, inflammation levels with IL-1β, CD68 and CD206 staining, angiogenesis and cell proliferation levels were assessed by CD31 and Ki67 staining. The levels of pathway-related proteins were analyzed by NLRP3 and Phospho-NF-κB P65 staining.ResultsNetwork pharmacology analysis identified key targets, encompassing HSP90AA1, STAT3, and PRKCB, involved in the AGEs-NF-κB-NLRP3 signaling axis. Molecular docking demonstrated strong binding affinity between AG components and these targets. In vitro, AG lessened AGEs-induced activation of the NLRP3 inflammasome via modulation of the NF-κB pathway and reinforced cell migration and angiogenesis. In vivo, AG-treated diabetic wounds exhibited accelerated healing, with augmented collagen deposition, lowered oxidative stress and inflammation, and strengthened cell migration and angiogenesis. AG promotes diabetic wound healing by modulating the AGEs-NF-κB-NLRP3 axis, exerting anti-inflammatory, antioxidant, pro-angiogenic, and cell-proliferative effects.ConclusionThis study provides new insights into diabetic wound repair and suggests that AG is a promising therapeutic agent for improving diabetic wound healing.